Optimalisasi Keterlibatan Orang Tua dalam Meminimalisir Nomophobia Pada Anak di Masa Pandemi Covid-19: The Optimizing Parental Involvement in Minimizing Nomophobia in Children During The Covid-19 Pandemic - Nikmatul Masruroh; Achmad Rifa'i; Aqila Abyani Rafitri; Fiki Anjani; Farikhatur Rohmah; Iqlil Sua'ibatul Islamiyah (Ngarsa: Journal of Dedication Based on Local Wisdom, 2022)
The COVID-19 pandemic leaves various problems in life, especially the problem of children's education. Children who should be able to experience school, meet friends and teachers during the learning process, are forced to learn from home using technology media, namely gadgets or cellphones or smartphones. The PSBB to PPKM policies have the impact of banning offline learning for students. So the selection of online learning must be done. So, it is inevitable that students must use gadgets to meet their needs in education. Students who in fact sit in elementary school every day have to look at their cellphones to find out the progress of learning given by their teachers at school. The problem of online learning creates nomophobia for children. Anxiety and fear when away from gadgets overshadows the psychology of children during the Covid 19 pandemic. From this problem, this article aims to provide an analysis of the assistance provided to mothers in Pasirian District, Lumajang Regency. This article describes the service activities carried out in Pasirian District in order to assist mothers to always be able to accompany their children in the learning process and be wise in using gadgets. This service uses the PAR technique, namely by using a ranking matrix of problems that will later be revealed from community activities. So it was agreed that the urgent problem to be solved was the existence of nomophobia. The results of this analysis stated that nomophobia can be solved by optimizing parental involvement in children's activities. Nomophobia can lead to mental disorders, so that the stages of completion are by first conducting parenting activities for mothers, then providing assistance to children in using gadgets and education in the wise use of gadgets. Pandemi covid 19 menyisakan berbagai persoalan dalam kehidupan, terutama masalah pendidikan anak. Anak-anak yang seharusnya bisa merasakan bangku sekolah, bertemu dengan teman dan gurunya pada saat proses pembelajaran, terpaksa harus belajar dari rumah dengan menggunakan media tekhnologi yaitu gadget atau handphone atau smartphone. Kebijakan PSBB sampai PPKM membawa dampak larangan pembelajaran secara luring bagi siswa. Sehingga pemilihan pembelajaran daring harus dilakukan. Sehingga, tak bisa dielakkan lagi siswa harus menggunakan gadget dalam memenuhi kebutuhannya dalam pendidikan. Siswa yang notabene duduk di bangku sekolah dasar setiap hari harus melihat handphonenya untuk mengetahui progress pembelajaran yang diberikan oleh gurunya di sekolah. Persoalan dari pembelajaran daring menciptakan nomophobia bagi anak-anak. Kecemasan dan ketakutan ketika berjauhan dari gadget membayangi psikologi anak-anak di masa pandemic Covid 19. Dari problem tersebut artikel ini bertujuan untuk memberikan analisis pada pendampingan yang dilakukan pada kaum ibu di Kecamatan Pasirian Kabupaten Lumajang. Artikel ini memaparkan kegiatan pengabdian yang dilakukan di Kecamatan Pasirian dalam rangka pendampingan kepada kaum ibu untuk selalu bisa mendampingi putera puterinya dalam proses pembelajaran serta bijak dalam penggunaan gadget. Pengabdian ini menggunakan teknik PAR, yaitu dengan menggunakan matrik ranking permasalahan yang nanti diungkap dari aktivitas masyarakat. Sehingga diperoleh kesepakatan bahwa masalah urgen yang harus dipecahkan adalah keberadaan nomophobia. Hasil dari analisis ini dinyatakan bahwa nomophobia bisa diselesaikan dengan cara optimalisasi keterlibatan orang tua dalam kegiatan anak. Nomophobia bisa mengakibatkan mental disorder, sehingga tahapan penyelesaiannya dengan melakukan kegiatan parenting terlebih dahulu kepada para ibu, kemudian dilakukan pendampingan pada anak-anak dalam penggunaan gadget serta edukasi dalam penggunaan gadget yang bijak.